Optimizing the Water and Nitrogen Management Scheme to Enhance Potato Yield and Water–Nitrogen Use Efficiency - Zhiqiang Ju; Dongrong Li; Yanqiang Cui; Dongyuan Sun (Agronomy, 2024)
Water and nitrogen are the primary constraints on improving agricultural productivity. The aims of this study are to investigate the synergistic effects of water and nitrogen, optimize their combination schemes under mulched drip irrigation systems in the northwest region of China, and offer scientific insight into enhancing water and nitrogen use efficiency in potato cultivation. The traditional cultivar “Qing Shu 10” was chosen for the test material. A two-year field study on potato water–nitrogen interaction was conducted in the central Hexi Corridor, within Ganzhou District of Zhangye City, with three irrigation levels (W1 (336 mm), W2 (408 mm), and W3 (480 mm)) and three nitrogen application rates (N1 (44 kg ha−1), N2 (192 kg ha−1), and N3 (240 kg ha−1)) using a fully randomized combination design, resulting in nine treatments. This study examined the varying responses in potato yield and water–nitrogen use efficiency to different water–nitrogen combinations in the Hexi Corridor region, developed a mathematical regression model to predict the economic benefit of potatoes based on water–nitrogen interactions, and refined the application strategy. The results indicated that both the volume of irrigation water and the rate of nitrogen application significantly influenced potato yield and water–nitrogen utilization efficiency. A distinct interactive effect was observed between irrigation volume and nitrogen application rate. The reduced irrigation volume restricted nitrogen uptake, with an average increase of 31.87% in nitrogen fertilizer partial productivity and 31.54% in potato yield when moving from W1 to W2 over two years and only a 6.02% and 5.48% increase from W2 to W3, respectively. Similarly, reduced nitrogen application rates also hindered water uptake by potatoes, with increases of 9.05% in water use efficiency, 12.14% in irrigation water use efficiency, 12.12% in yield from N1 to N2, and only 1.98% and 1.69% increases in irrigation water use efficiency and yield from N2 to N3, while water use efficiency decreased by 1.17%. The highest yield values over the two-year period were observed in the N2W3 treatment, with 43,493.54 and 43,082.19 kg ha−1. The irrigation volume, nitrogen application rate, and potato economic benefit were well modeled by a quadratic regression, with an R2 of 0.996 for both predicted and actual economic benefit over two years, indicating a trend of initial increase followed by a decrease as water and nitrogen levels increased. Through simulation optimization and a thorough analysis of multiple indicators, the N2W3 treatment yielded an economic benefit exceeding 25,391.13 CNY ha−1 and demonstrated a high water–nitrogen utilization efficiency. This treatment not only enhances potato economic benefit but also minimizes agricultural resource inputs, establishing it as the optimal water and fertilizer management strategy for this study.